CATIA V5 : macro programming with Visual Basic script - Ziethen, Dieter R. (McGraw-Hill, 2013)
"Write powerful, custom macros for CATIA V5: macro programming with visual basic script shows you, step by step, how to create your own macros that automate repetitive tasks, accelerate design procedures, and automatically generate complex geometries. Filled with full-color screenshots and illustrations, this practical guide walks you through the entire process of writing, storing, and executing reusable macros for CATIA V5. Sample Visual Basic Script code accompanies the book?s hands-on exercises and real-world case studies demonstrate key concepts and best practices. Coverage includes: CATIA V5 macro programming basics Communication with the environment Elements of CATParts and CATProducts 2D wireframe geometry 3D wireframe geometry and surfaces Solid features Object classes VBScript commands."--